Heterogeneous Escape from X Chromosome Inactivation Results in Sex Differences in Type I IFN Responses at the Single Human pDC Level - Hagen, Sven Hendrik (Cell Rep, 2020)
Immune responses differ between women and men, and type I interferon (IFN) responses following Toll-like receptor 7 (TLR7) stimulation are higher in women. The precise mechanisms driving these sex differences in immunity are unknown. To investigate possible genetic factors, we quantify escape from X chromosome inactivation (XCI) for TLR7 and four other genes (RPS6KA3, CYBB, BTK, and IL13RA1) at the single plasmacytoid dendritic cell (pDC) level. We observe escape from XCI for all investigated genes, leading to biallelic expression patterns. pDCs with biallelic gene expression have significantly higher mRNA levels of the respective genes. Unstimulated pDCs with biallelic TLR7 expression exhibit significantly higher IFNα/β mRNA levels, and IFNα exposure results in significantly increased IFNα/β protein production by pDCs. These results identify unanticipated heterogeneity in escape from XCI of several genes in pDCs and highlight the important contribution of X chromosome factors to sex differences in type I IFN responses, which might explain observed sex differences in human diseases.